TG-DSC investigation of co-combustion characteristics of blends sawdust and coal. Issue 1 (May 2021) - Umar, D F; Monika, I; Handoko, S
Abstract: Co-combustion of biomass and coal in coal fired power plant could reduce CO2 emissions and utilize renewable energy resources. To understand the co-combustion characteristics of biomass and coal blends, thermogravimetry-differential scanning calorimetry (TG-DSC) analysis, as well as proximate, ultimate and heating value have been conducted. TG-DSC measures both weight changes (TG) and heat flow (DSC) in a material as a function of temperature or time in a controlled atmosphere. The combustion profiles can be used to study some combustion properties of fuels and fuel blends. The biomass that used in this study was sawdust in its origin and torrefied sawdust which blend with a low rank coal. The composition of the biomass and coal were 1:3; 1:1 and 3:1 in weight ratio. Results indicated that the blend of coal and torrefied sawdust in weight ratio of 1:3 was the best combustion performance compared to the other composition, indicated by the highest of ignition temperature (Tig), maximum combustion rate (Rmax) and heating value.